Appendiceal stump phlegmon: a rare case - Rodríguez-Gutiérrez, María Manuela (2025)
Stump appendicitis is a rare late complication following appendectomy that poses a diagnostic challenge, as physicians are often not very familiar with this pathology. This fact leads to complications, such as intestinal fistula and small bowel obstruction, among others. Appendiceal phlegmon is an evolutionary form of acute appendicitis whose frequency is quite low. It requires surgical treatment, but there is still no consensus on the therapeutic protocol.Our case involves a female patient who had undergone appendectomy years ago, who consulted for right iliac fossa pain, emesis, febrile episodes and signs of peritoneal irritation. Therefore, she was taken to exploratory laparotomy, revealing a mass in the ascending colon, from which a biopsy was taken. This reported appendiceal stump phlegmon, which was treated.Currently, appendiceal stump phlegmon is not yet considered a possible differential diagnosis in patients with right iliac fossa pain who have undergone appendectomy. For this reason, the diagnosis may be delayed, and complications such as acute abdomen, perforation and sepsis may occur. Stump appendectomy is the treatment of choice for patients with stump appendicitis. The objective of this case report is to highlight the importance of this pathology, given its low incidence. Clinicians should be aware of the possibility of stump appendicitis or, in the case of the patient with phlegmon, should confirm any clinical suspicion through radiological imaging to quickly recognize this pathology and prevent related complications.